Strategi Orang Tua Mendidik Anak Usia Dini dalam Mengamalkan Nilai-Nilai Pancasila - Maulana Arafat Lubis; Nisha Marina; Hamidah Hamidah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Pancasila is the basis of the state that must be upheld by practicing its values in everyday life. The good behavior of a nation is also a mirror for the country in front of other countries. This study aims to determine how parents' strategy in educating their early children instills Pancasila values when not at school or at home. The research method used is qualitative with a phenomenological study approach. Sources of data in this study were parents of early childhood. Determination of data sources using a purposive sampling technique. Data collection using interviews. Data analysis was carried out, including data reduction, data presentation, and conclusions. After being analyzed, the data were interpreted and tested for validity using member-checking techniques. The study results found that each parent has a similar strategy for educating their children to practice the values of Pancasila in everyday life. Education that parents teach children to practice the values of Pancasila, such as introducing religion to children, teaching children to worship, teaching children to love others, teaching children, practicing cooperation, inviting children to consult, teaching children always to accept decisions if it is for the common good, discuss anything for fairness, teach children to learn continually, and teach children always to respect the work of others